BS EN IEC 62803-3. Transmitting and receiving equipment for radiocommunication. Frequency response of optical-to-electric conversion device in high-frequency radio over fibre systems. Part 3. Measurement method of nonlinear response of optical-to-electric converter (19th November 2021) - British Standards Institution,
No abstract available